Next-generation touch-interface for statina acoustic holography - Cao, Lu Yan (2010)
In the past, it had been demonstrated that nearfield acoustical holography (NAH) was a useful tool for visualizing noise sources in automotive and aircraft industries. Thus NAH would be a good practice to reconstruct a source field in the next generation of touch interface. Planar is one of the two most widely used among the various nearfield acoustical holography techniques. Therefore, the implementation of NAH in planar coordinate had been used for this project. Its performance in plastic board and ideal simulating environment will be analyzed in this report.